Dysrhythmias in patients with a complete atrioventricular septal defect: From surgery to early adulthood - Houck, Charlotte A. (Congenit Heart Dis, 2018)
OBJECTIVE: Outcomes after surgical repair of complete atrioventricular septal defect (cAVSD) have improved. With advancing age, the risk of development of dysrhythmias may increase. The aims of this study were to (1) examine development of sinus node dysfunction (SND), atrial and ventricular tachyarrhythmias, and (2) study progression of atrioventricular conduction abnormalities in young adult patients with repaired cAVSD. STUDY DESIGN: In this retrospective multicenter study, 74 patients (68% female) with a cAVSD repaired in childhood were included. Patients’ medical files were evaluated for occurrence of SND, atrioventricular conduction block (AVB), atrial and ventricular tachyarrhythmias. RESULTS: Median age at repair was 6 months (interquartile range 3‐10) and median age at last follow‐up was 24 years (interquartile range 21‐28). SND occurred after a median of 17 years (interquartile range 11‐19) after repair in 23% of patients, requiring pacemaker implantation in two patients (12%). Regular supraventricular tachycardia was observed in three patients (4%). Atrial fibrillation and ventricular tachyarrhythmias were not observed. Twenty‐seven patients (36%) had first‐degree AVB, which was self‐limiting in 16 (59%) and persistent in 10 (37%) patients. One patient developed third‐degree AVB 7 days after left atrioventricular valve replacement. Spontaneous type II second‐degree AVB occurred in a 28‐year‐old patient. Both patients underwent pacemaker implantation. CONCLUSIONS: Clinically significant dysrhythmias were uncommon in young adult patients after cAVSD repair. However, three patients required pacemaker implantation for either progression of SND or spontaneous type II second‐degree AVB. Longer follow‐up should point out whether dysrhythmias will progress or become more prevalent with increasing age.